The Addition Of Jicama Flour On The Quality Of Shape, Color, Aroma, Texture And Taste In Muffins - Sari, Febrita; Gusnita, Wiwik; Kasmita, Kasmita; Anggraini, Ezi (Universitas Negeri Padang, 2024)
Muffins are a type of bread without yeast that are made in personal sizes and can be eaten in just a few bites. Muffins that are generally developed at this time are classified as quick bread because they use chemical raising agents that can react quickly as a substitute for yeast which is a biological raising agent that reacts more slowly. In this research, the main ingredients in making muffins are wheat flour, sugar, eggs, fat, baking powder and liquid. Jicama flour is flour that comes from jicama tubers that are dried, ground, then sifted to become flour. Currently, there are many innovations in muffin recipes both in terms of taste and raw materials for making them. The city of Padang is the area that produces the most jicama in West Sumatra, but it is still limited in terms of processing because jicama is usually only consumed fresh. Thus, to optimize the processing, especially for jicama fruit which is no longer attractive to sell because the skin color has started to turn black, the author wants to use it by processing it into flour which will be substituted in muffins. This research aims to analyze the effect of 15%, 30% and 45% substitution of jicama flour on the quality of shape, color, aroma, texture and taste of the muffins produced. The type of research used in this research is pure experiment (True Experiment) with organoleptic tests. The research was carried out 3 times with 4 treatments each and tested on 3 expert panelists. Then the data obtained was tabulated in table form and analysis of variance (ANOVA) was carried out. If they differed, they were tested using the Duncan Multi Ranges Test (DMRT). Then data analysis is carried out, if the data obtained by Fcount is greater than Ftable then proceed with the Duncan test. Muffins with jicama flour substitution had the best results at 15% treatment (X1).